Scoping Review of Verbal De-Escalation in Psychiatric Emergency - Pragholapati, Andria; Fitrikasari, Alifiati; Handayani, Fitria; Kristina, Tri Nur; Dewi, Nur Setiawati; Winarni, Tri Indah (GLOBAL HEALTH SCIENCE GROUP, 2024)
This article presents an in-depth literature review on the practices and significance of verbal de-escalation in psychiatric emergency situations. Verbal de-escalation is a communication strategy aimed at reducing tension and conflict in psychiatric patients experiencing crises. The aim of this research is to explore the effectiveness of various training methods in implementing verbal de-escalation techniques in psychiatric emergencies. The research method with scoping review, this article provides an overview of the concept of verbal de-escalation, commonly used techniques, and its positive impact on enhancing safety and intervention effectiveness in psychiatric emergencies. Additionally, the article identifies factors influencing the success of implementing verbal de-escalation and emphasizes the need for training and a holistic approach in managing psychiatric emergencies. The findings of this research can offer insights for practitioners, researchers, and policymakers in improving the quality of psychiatric emergency services through the effective implementation of verbal de-escalation strategies.